Handbook of research on new product development - Golder, Peter N.; Mitra, Debanjan (Edward Elgar Publishing, 2018)
New products are the major driver of revenue growth in today's dynamic business environment. In this Handbook, the world's foremost experts on new product development bring together the latest thinking on this vitally important topic. These thought-leading authors organize knowledge into useful and insightful frameworks covering all aspects of new product development: companies, collaborators, customers, context, markets, and performance. Managers will benefit from the handbook by expanding their knowledge of new product development and researchers will learn about opportunities to continue ex.